Expanding the Outreach of Financial Services : The Experience of Financial Institutions - World Bank (Washington, DC, 2013)
In 2007-08 Da Afghanistan Bank (DAB), the central bank of Afghanistan, was in the process of reforming the financial sector. While some considerable advances have been made with respect to basic legislation, some central banking reform, the introduction of new currency, and the beginnings of a microfinance sector, much work still remains to be done. These case studies examine the experience of the following five different groups of financial market participants operating in Afghanistan: reputable private investors; small and medium entrepreneurs; BRAC, a microfinance institution; Kabul Bank, a fast growing commercial bank; and Bank Millie, a state-owned bank. The examination of each institution will address the factors that have facilitated expansion and the constraints it has faced in further expanding financial services. This report also analyses the constraints and opportunities that are common to one, several or all of these financial market participants, and concludes with recommendations from the perspectives of these institutions.